Canadian Response to Fluctuations in United States Prices - McPheters, Lee R.; Stronge, William B. (The Review of Economics and Statistics, 1976)
T HIS paper utilizes cross spectral analysis to examine the relationship between consumer price movements in the United States and Canada. We hope to shed light on the extent of the of the cost of living in Canada on that of the United States. Although a number of very competent studies have been undertaken which deal with the nature of economic interdependence between the two countries (among others, see Brecher and Reisman, 1957; Bryce, 1939; Chambers, 1958; Gibson, 1956; Rosenbluth, 1957; and Wonnacott, 1961), specific questions of timing and amplitude characteristics of consumer price series over cycles of varying length have yet to be fully explored. A recent article by Bonomo and Tanner applied spectral analysis to industrial production series for the two countries and found statistically significant relations between American and Canadian economic cycles of lengths between 3 and 100 months (1972, p. 7.). Following Wonnacott's observations that production and price indices may very well be viewed as alternative indicators of dependence (1961, p. 6), we propose to test for the existence of significant relationships in U.S. and Canadian prices to further explore the nature of the hypothesized Canadian dependence on the United States. In section II, we discuss some considerations involved in the use of spectral analysis. Section III reviews the empirical findings, and section IV contains our conclusions. II. A Brief Overview of Spectral Analysis